Epidemiological and Clinico-Mycological Aspects of Pityriasis Versicolor in Tripoli-Central Hospital - Talal Douzan; Hamida Al-Dwibe; Safa Sharfuldeen; Altaahir Almihabas (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Pityriasis versicolor (PV) is a common worldwide superficial fungal infection of the skin, caused by several species of a lipophilic dimorphic fungus, Malassezia. Usually presents with well-defined scaly hypopigmented or hyperpigmented macules and patches on seborrheic sites of body. The study was aimed to determine epidemiological, clinical and mycological profile of PV among patients attending out-patient dermatology clinic in Tripoli Central Hospital (TCH). Methods. A descriptive cross-sectional study was carried in a TCH for one year period in which 110 patients with skin lesions suspected to be PV were studied. Diagnosis of cases was done by using woods lamp and by direct microscopy using 10% KOH and cello-tape method. Result. Of 110 suspected cases of PV, 51.82% were females and 48.18% were males, with slight female preponderance (F:M = 1.08:1). The age of patients was ranged from 8 to 70 years, with a mean age 26.2 years. High frequency of infection (54.55%) was reported among age group 16–25 years and frequency of disease was inversely associated with older age (2.7%). The disease mostly reported among Libyans (95.6%), outdoor workers (54%), students (48.2%), 31.8% had positive family history of disease, 81.8% had negative past medical history, 80% hadn’t associated skin disease, 80.9% hadn’t drug history, and 52.7% had used treatment previously. Majority of cases (87%) were complained from cosmetic effect and 57.3% from itching. Most (54.6%) of them were presented with hyperpigmented lesions, that different in size and shape. The back, chest, back of the neck and arms were most common affected sites with a frequency of (60%, 50.9%, 51.8% & 42.7%, respectively), and symptoms were aggravated in summer time. KOH mount test has the higher diagnostic value (80%) followed by wood’s lamp (77%), and cello-tap (71%). Conclusion. Study concluded that the clinic-mycological and epidemiological parameters on PV does not differ significantly from those observed by other studies. The KOH test was positive in most of the cases, which makes it suitable to be used than Cello-tape in diagnosis and confirmation of PV.